Impact of Natural Farming Cropping System on Rural Households—Evidence From Solan District of Himachal Pradesh, India - Laishram, Chinglembi; Vashishat, Rohit Kumar; Sharma, Subhash; Rajkumari, Bhavna; Mishra, Neha; Barwal, Parul; Vaidya, Manoj Kumar; Sharma, Ravinder; Chandel, Rajeshwar Singh; Chandel, Ashu; Gupta, Rakesh Kumar; Sharma, Neha (Frontiers in Sustainable Food Systems, 2022)
Natural farming, popularly known as zero budget natural farming, is an innovative farming approach. It is low input based, climate resilient, and low cost farming system because all the inputs (insect repellents, fungicides, and pesticides) are made up of natural herbs and locally available inputs, thereby reducing the use of artificial fertilizers and industrial pesticides. It is becoming increasingly popular among the smallholder farmers of Himachal Pradesh. Under the natural farming system, 3 to 12 crops are cultivated together on the same area, along with leguminous crops as intercrop in order to ensure that no piece of land is wasted and utilized properly. This article focuses mainly on the different cropping systems of natural farming and comparing the economics of natural farming (NF) with conventional farming (CF) systems. Study shows that farmers adopted five major crop combinations under natural farming system, i.e., vegetables-based cropping system (e.g., tomato + beans + cucumber and cauliflower + pea + radish), vegetables-cereals-based cropping system, and other three more cropping systems discussed in this article. The results indicated that a vegetable-based cropping system has 19.68% more net return in Kharif season and 24.64% more net return in Rabi season as compared to conventional farming vegetable-based monocropping system. NF maximizes land use and reduces the chance of crop yield loss. NF has resulted in increased returns especially in the vegetable cropping system where reduction in cost was 30.73 per cent (kharif) and 11.88 per cent (rabi) across all crop combinations in comparison to CF. It is found in study that NF was cost savings from not using chemical fertilizers and pesticides, as well as higher benefit from intercrops.